Characterization of AMA1‐RON2L complex with native gel electrophoresis and capillary isoelectric focusing. Issue 3 (21st November 2021) - Zhu, Daming; Dai, Weili; Srinivasan, Prakash; McClellan, Holly; Braden, Dennis; Allee‐Munoz, Alec; Hurtado, Patricia A. Gonzales; Miller, Louis H.; Duffy, Patrick E.
Abstract: Rhoptry neck protein 2 (RON2) binds to the hydrophobic groove of apical membrane antigen 1 (AMA1), an interaction essential for invasion of red blood cells (RBCs) by Plasmodium falciparum (Pf) parasites. Vaccination with AMA1 alone has been shown to be immunogenic, but unprotective even against homologous challenge in human trials. However, the AMA1‐RON2L (L is referred to as the loop region of RON2 peptide) complex is a promising candidate, as preclinical studies with Freund's adjuvant have indicated complete protection against lethal challenge in mice and superior protection against virulent infection in Aotus monkeys. To prepare for clinical trials of the AMA1‐RON2L complex, identity and integrity of the candidate vaccine must be assessed, and characterization methods must be carefully designed to not dissociate the delicate complex during evaluation. In this study, we developed a native Tris‐glycine gel method to separate and identify the AMA1‐RON2L complex, which was further identified and confirmed by Western blotting using anti‐AMA1 monoclonal antibodies (mAbs 4G2 and 2C2) and anti‐RON2L polyclonal Ab coupled with mass spectrometry. The formation of complex was also confirmed by Capillary Isoelectric Focusing (cIEF). A short‐term (48 h and 72 h at 4°C) stability study of AMA1‐RON2L complex was also performed. The results indicate that the complex was stable for 72 h at 4°C. Our research demonstrates that the native Tris‐glycine gel separation/Western blotting coupled with mass spectrometry and cIEF can fully characterize the identity and integrity of the AMA1–RON2L complex and provide useful quality control data for the subsequent clinical trials.